The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/sef-10-2012-0118
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the performance of pension funds: evidence from UK

Abstract: Purpose – This paper aims to examine the investment performance of pension funds in the UK using the three standard performance measurement models, the capital asset pricing model (CAPM), Fama-French model and the Carhart model. Design/methodology/approach – The authors use the CAPS-Mellon survey data for the period 1990-2008 and employ the three standard performance measurement models, the CAPM, Fama-French model and the Carhart model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…Trimech et al (2009) noted the estimated size effect was more pronounced for small portfolios than for big ones. Adami et al(2014) in UK, also found similar results by revealing that the SMB coefficients were all positive indicating that in a given month the small capitalization stocks outperformed the large cap stocks. The size co-efficient values of all the deciles were found to be similar.…”
Section: Smbsupporting
confidence: 57%
“…Trimech et al (2009) noted the estimated size effect was more pronounced for small portfolios than for big ones. Adami et al(2014) in UK, also found similar results by revealing that the SMB coefficients were all positive indicating that in a given month the small capitalization stocks outperformed the large cap stocks. The size co-efficient values of all the deciles were found to be similar.…”
Section: Smbsupporting
confidence: 57%
“…Disadvantage of many above-mentioned fund studies in CEE is that analysis and comparisons of performance comparison is conducted through Sharpe ratio (Sharpe, 1994), CAPM (Sharpe, 1964), Sortino ratio (Sortino & Van Der Meer, 1991), Jensen's alpha (Jensen, 1968) or Treynor ratio (Treynor, 1965). Recent studies such as those comparing performance of green funds with that of standard funds (Leite & Cortez, 2014;Silva & Cortez, 2016;Marti-Ballester, 2019, or studies focusing on comparative performance of funds in regions other than CEE (Adami et al, 2014;Boubakri et al, 2016;Sha & Gao, 2019) use Fama and French three-factor or five-factor models (Fama & French, 1993, 2015 or Carhart's model (Carhart, 1997). Analysis of funds data from CEE using this methodology would be interesting as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The returns have been calculated gross of taxes and expenses due to the lack of availability in historical data for expense ratio and managerial fees. The whole sample has then been sorted by historical Assets under Management as indicator of historical size of the investment trust, as performed by Adami et al (2014).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Lately, Blanco (2012) as well as Bhatnagar and Ramlogan (2012) investigated the empirical failure of CAPM compared with Fama-French Three Factor model, demonstrating the superiority of the multi factor model. Adami et al (2014), applied CAPM, Fama-French three factor and Fama-French Carhart (1997) models evaluating the performances of UK pension funds (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) finding that the models are significant in explaining the abnormal returns and that the Carhart momentum factor did not add significant effect to the model providing significantly greater alpha values. Fama and French (2015), described five risk factors common in the returns on stock and bonds, and among these, three are related to the stock market: firm size, book-to-market equity and overall market; and two are related to the bond market: maturity and default risk (Note 2) and developed the most commonly used performance measurement model, the Fama-French Three (1993) andFive Factor Models (2015).The most recent five-factor model is directed to capture the value, profitability, investment patterns and size in returns, and it has been proved performing better than the Fama-French Three-Factor model (Fama and French, 2015).…”
Section: Level Of Risk (Note 1)mentioning
confidence: 99%